1997
DOI: 10.4265/bio.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities to Hydrogen Peroxide Vapor of Intact and Decoated Spores of Bacillus subtilis As Influenced by Divalent Cations Supplemented in Sporulation Medium.

Abstract: We developed Mn-supplemented, Fe-supplemented , and Ca-supplemented spores of Bacillus subtilis 168 and ATCC9372 in the respective presence of manganese , ferric and calcium ions, and compared their resistance to vapor-phase hydrogen peroxide with that to aqueous phase hydrogen peroxide and heat. Mn-supplemented spores were the most sensitive to heat and hydrogen peroxide solution but was the most resistant to vapor-phase hydrogen peroxide at low relative humidities as compared with Fe-supplemented and Ca-supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Spores were harvested (when 90% of the cells had sporulated) by centrifugation at 7000 × g for 20 min at 4°C. The resultant spores were treated with lysozyme (1 mg ml −1 , Sigma Chemical Co., St Louis, MO, USA) and washed with 50 mmol l −1 potassium phosphate buffer at pH 7·0 as described previously (Tsuchida and Tsuchido 1997). The spores suspended in sterile distilled water were frozen and stored at −84°C until use.…”
Section: Spore Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spores were harvested (when 90% of the cells had sporulated) by centrifugation at 7000 × g for 20 min at 4°C. The resultant spores were treated with lysozyme (1 mg ml −1 , Sigma Chemical Co., St Louis, MO, USA) and washed with 50 mmol l −1 potassium phosphate buffer at pH 7·0 as described previously (Tsuchida and Tsuchido 1997). The spores suspended in sterile distilled water were frozen and stored at −84°C until use.…”
Section: Spore Productionmentioning
confidence: 99%
“…A previous work studied the heat resistance of B. subtilis spores in different oils (Nakagawa et al. 1998) and also the effects of hydrogen peroxide and divalent cations in the sporulation medium (Tsuchida and Tsuchido 1997). Such data generated in oil and buffer systems are important in the construction of thermal inactivation databases mimicking the actual food systems.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it may not be possible to extrapolate previous studies of aqueous H 2 O 2 sterilization to what occurs on spore deactivation with H 2 O 2 in an SCCO 2 phase. Decades of study on H 2 O 2 sterilization have revealed that the damage to the spores depends on concentration and whether H 2 O 2 is in the liquid or vapor state (King and Gould, 1969, Shin et al, 1994, Tsuchida and Tsuchido, 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide solutions were prepared by mixing food grade concentrated hydrogen peroxide (50% w/w) (Peróxidos do Brasil Ltda, Curitiba, Brazil) with sterile deionized water and used on the same day (Tsuchida & Tshuchido, 1997). The concentration of the diluted solutions was checked before their use as proposed by Buchen and Marth (1977).…”
Section: Preparation Of Hydrogen Peroxide Solutionsmentioning
confidence: 99%